Traction maculopathies – pathogenesis and diagnostics - Wylęgała, Edward; Woyna-Orlewicz, Anna; Piłat, Jarosław; Teper, Sławomir; Ludyga, Aneta (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
Traction maculopathies are a group of age-related degenerative diseases characterized by pathology of vitreomacular interface including idiopathic epimacular membranes, vitreomacular traction syndrome and idiopathic macular hole. The disorders develop due to mechanical forces caused by focal condensation or incomplete detachement of vitreous and shrinkage of pathological membranes. The forces can be tangential to retinal surface in epiretinal membranes, anterior-posterior in vitreomacular traction syndrome and oblique (trampoline) in idiopathic macular hole. Authors discuss pathogenesis and diagnostics of traction maculopathies with use of optical coherence tomography and microperimetry, based on current literature. This work presents also idiopathic macular hole classification with use of optical coherence tomography images compared with biomicroscopic classification by Gass.